Cardiac remodeling in response to 1 year of intensive endurance training - Arbab-Zadeh, Armin; Perhonen, Merja; Howden, Erin; Peshock, Ronald M; Zhang, Rong; Adams-Huet, Beverly; Haykowsky, Mark J; Levine, Benjamin D (Circulation (New York, N.Y.), 2014)
It is unclear whether, and to what extent, the striking cardiac morphological manifestations of endurance athletes are a result of exercise training or a genetically determined characteristic of talented athletes. We hypothesized that prolonged and intensive endurance training in previously sedentary healthy young individuals could induce cardiac remodeling similar to that observed cross-sectionally in elite endurance athletes. Twelve previously sedentary subjects (aged 29±6 years; 7 men and 5 women) trained progressively and intensively for 12 months such that they could compete in a marathon. Magnetic resonance images for assessment of right and left ventricular mass and volumes were obtained at baseline and after 3, 6, 9, and 12 months of training. Maximum oxygen uptake ( max) and cardiac output at rest and during exercise (C2H2 rebreathing) were measured at the same time periods. Pulmonary artery catheterization was performed before and after 1 year of training, and pressure-volume and Starling curves were constructed during decreases (lower body negative pressure) and increases (saline infusion) in cardiac volume. Mean max rose from 40.3±1.6 to 48.7±2.5 mL/kg per minute after 1 year (P<0.00001), associated with an increase in both maximal cardiac output and stroke volume. Left and right ventricular mass increased progressively with training duration and intensity and reached levels similar to those observed in elite endurance athletes. In contrast, left ventricular volume did not change significantly until 6 months of training, although right ventricular volume increased progressively from the outset; Starling and pressure-volume curves approached but did not match those of elite athletes. One year of prolonged and intensive endurance training leads to cardiac morphological adaptations in previously sedentary young subjects similar to those observed in elite endurance athletes; however, it is not sufficient to achieve similar levels of cardiac compliance and performance. Contrary to conventional thinking, the left ventricle responds to exercise with initial concentric but not eccentric remodeling during the first 6 to 9 months after commencement of endurance training depending on the duration and intensity of exercise. Thereafter, the left ventricle dilates and restores the baseline mass-to-volume ratio. In contrast, the right ventricle responds to endurance training with eccentric remodeling at all levels of training.